Conditional expression of the ubiquitous transcription factor MafK induces erythroleukemia cell differentiation. - Igarashi, K (1995)
Transcription factor NF-E2 activity is thought to be crucial for the transcriptional regulation of many erythroid-specific genes. The three small Maf family proteins (MafF, MafG, and MafK) that are closely related to the c-Maf protooncoprotein constitute half of the NF-E2 activity by forming heterodimers with the large tissue-restricted subunit of NF-E2 called p45. We have established and characterized murine erythroleukemia cells that conditionally overexpress MafK from a metallothionein promoter. The conditional expression of MafK caused accumulation of hemoglobin, an indication of terminal differentiation along the erythroid pathway. Concomitantly, DNA binding activities containing MafK were induced within the MafK-overexpressing cells. These results demonstrate that MafK can promote the erythroid differentiation program in erythroleukemia cells and suggest that the small Maf family proteins are key regulatory molecules for erythroid differentiation.